Impact of mHealth interventions for reproductive, maternal, newborn and child health and nutrition at scale: BBC Media Action and the Ananya program in Bihar, India - Ward, Victoria C; Raheel, Hina; Weng, Yingjie; Mehta, Kala M; Dutt, Priyanka; Mitra, Radharani; Sastry, Padmapriya; Godfrey, Anna; Shannon, Melissa; Chamberlain, Sara; Kaimal, Rajani; Carmichael, Suzan L; et al. (Journal of global health, 2020)
Mobile health (mHealth) tools have potential for improving the reach and quality of health information and services through community health workers in low- and middle-income countries. This study evaluates the impact of an mHealth tool implemented at scale as part of the statewide reproductive,maternal, newborn and child health and nutrition (RMNCHN) program in Bihar, India. Three survey-based data sets were analysed to compare the health-related knowledge, attitudes and behaviours amongst childbearing women exposed to the Mobile and Dr. Anita mHealth tools during their visits with frontline workers compared with those who were unexposed. An evaluation by Mathematica (2014) revealed that exposure to Mobile and Dr. Anita recordings were associated with significantly higher odds of consuming iron-folic acid tablets (odds ratio (OR) = 2.3, 95% confidence interval (CI) = 1.8-3.1) as well as taking a set of three measures for delivery preparedness (OR = 2.8, 95% CI = 1.9-4.2) and appropriate infant complementary feeding (OR = 1.9, 95% CI = 1.0-3.5). CARE India's Community-based Household Surveys (2012-2017) demonstrated significant improvements in early breastfeeding (OR = 1.64, 95% CI = 1.5-1.78) and exclusive breastfeeding (OR = 1.46, 95% CI = 1.33-1.62) in addition to birth preparedness practices. BBC Media Action's Usage & Engagement Survey (2014) demonstrated a positive association between exposure to Mobile and Dr. Anita and exclusive breastfeeding (58% exposed vs 43% unexposed, < 0.01) as well as maternal respondents' trust in their frontline worker. Significant improvements in RMNCHN-related knowledge and behaviours were observed for Bihari women who were exposed to Mobile and Dr. Anita. This analysis is unique in its rigorous evaluation across multiple data sets of mHealth interventions implemented at scale. These results can help inform global understanding of how best to use mHealth tools, for whom, and in what contexts. ClinicalTrials.gov number NCT02726230.